ChemInform Abstract: Facile Access to Fluoromethylated Arenes by Nickel‐Catalyzed Cross‐Coupling Between Arylboronic Acids and Fluoromethyl Bromide. Issue 48 (December 2015) - An, Lun; Xiao, Yu‐Lan; Min, Qiao‐Qiao; Zhang, Xingang
Abstract: The title reaction proceeds under mild conditions and exhibits excellent functional group compatibility.